2021
DOI: 10.1108/sgpe-08-2020-0061
|View full text |Cite
|
Sign up to set email alerts
|

“I felt like I was not just a student:” examining graduate student learning at academic and professional conferences

Abstract: Purpose The purpose of this study is to explore what new knowledge is gained at academic and professional conferences by describing how this knowledge complements or contradicts campus-based learning and previous experiences of graduate students. Through gaining insights into conference-based learning, researchers and policymakers can create more complex and dynamic graduate student learning experiences and design conferences that welcome and encourage graduate student perspectives and voices. Design/methodo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…We also recommend that public platforms such as poster sessions and brown bag seminars be developed to support individualized student boundary spanning. Like the outcomes of graduate student participation in conventional academic conferences (Campbell et al , 2021), such platforms would enable the dissemination of experiences and knowledge and help students develop stronger senses of “fit” between their individual values, interests and goals, boundary spanning activities and doctoral programs. Here again, we suggest that these platform-types be student-led, albeit with faculty endorsement and collaboration, to further foster student agency.…”
Section: Discussionmentioning
confidence: 99%
“…We also recommend that public platforms such as poster sessions and brown bag seminars be developed to support individualized student boundary spanning. Like the outcomes of graduate student participation in conventional academic conferences (Campbell et al , 2021), such platforms would enable the dissemination of experiences and knowledge and help students develop stronger senses of “fit” between their individual values, interests and goals, boundary spanning activities and doctoral programs. Here again, we suggest that these platform-types be student-led, albeit with faculty endorsement and collaboration, to further foster student agency.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of participants were experienced teachers with an average of 10 years of teaching experience (AlQorin, 2022;Yusuf, 2021). Of the 50 teachers who attended the conference, 80% reported that they found the conference to be effective in improving their readiness to implement the Merdeka Belajar curriculum (Campbell et al, 2021;Widayat et al, 2023).…”
Section: Methodsmentioning
confidence: 99%